2022
DOI: 10.1021/acs.langmuir.2c00905
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Folate-Conjugated and pH-Responsive Cell Membrane Mimetic Mixed Micelles for Desirable DOX Release and Enhanced Tumor-Cellular Target

Abstract: Smart multifunctional polymeric micelles are in urgent demand for future cancer diagnosis and therapy. In this paper, doxorubicin (DOX)-loaded folic acid (FA)-targeting and pH-responsive cell membrane mimetic mixed micelles of P­(DMAEMA-co-MaPCL) (PCD) and FA-P­(MPC-co-MaPCL) (PMCF) (mass ratio 5/5) were prepared by a dialysis method. The micelle size, morphology, X-ray powder diffraction (XRD), pH responsiveness, in vitro DOX release, cytotoxicity, and cellular uptake were studied in detail. The results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…While the blank PEG–PCL micelles presented with a hydrodynamic diameter ( D h ) of 42 ± 1 nm (PDI = 0.11), there was a moderate increase to 53 ± 1 nm (PDI = 0.15) for the PEG–PCL–OVP 0.3 micelles consistent with OVP encapsulation (Figure b). In comparison, a doubling or greater in size is often reported for the preparation of mixed micelles as compared to their respective non-responsive copolymer micelles. To provide an indication of the stability of the micelles in solution, the D h was measured again after 42 days, which revealed an increase of 20–30% for the PEG–PCL ( D h = 52 ± 2 nm, PDI = 0.18) and PEG–PCL–OVP 0.3 micelles ( D h = 71 ± 2 nm, PDI = 0.23) and implied that the encapsulation of OVP has negligible influence on the micelle stability (SI, Figure S5). Modeling of the SAXS profiles revealed that the blank and OVP-loaded micelles adopted oblate ellipsoidal morphologies in PBS at pH 7.4 (SI, Tables S5 and S6).…”
Section: Resultsmentioning
confidence: 99%
“…While the blank PEG–PCL micelles presented with a hydrodynamic diameter ( D h ) of 42 ± 1 nm (PDI = 0.11), there was a moderate increase to 53 ± 1 nm (PDI = 0.15) for the PEG–PCL–OVP 0.3 micelles consistent with OVP encapsulation (Figure b). In comparison, a doubling or greater in size is often reported for the preparation of mixed micelles as compared to their respective non-responsive copolymer micelles. To provide an indication of the stability of the micelles in solution, the D h was measured again after 42 days, which revealed an increase of 20–30% for the PEG–PCL ( D h = 52 ± 2 nm, PDI = 0.18) and PEG–PCL–OVP 0.3 micelles ( D h = 71 ± 2 nm, PDI = 0.23) and implied that the encapsulation of OVP has negligible influence on the micelle stability (SI, Figure S5). Modeling of the SAXS profiles revealed that the blank and OVP-loaded micelles adopted oblate ellipsoidal morphologies in PBS at pH 7.4 (SI, Tables S5 and S6).…”
Section: Resultsmentioning
confidence: 99%
“…Polymeric micelles are a kind of nanoparticles that have potential application prospect in anticancer drug delivery, owing to their advantages such as drug solubilization, good permeability, long time circulation in vivo , and easy functional modification. By introduction of pH-sensitive groups, temperature-sensitive groups, redox-sensitive groups, etc., various stimulus-responsive polymeric micelles can be prepared. They can take advantage of the difference between the normal cellular microenvironment (pH ≈ 7.4, 36–37 °C, low glutathione (GSH)) and the tumor tissue microenvironment (pH ≈ 5.0–6.5, 37–42 °C, high GSH) to achieve the controlled release of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…DOX is a type of cell cycle nonspecific anthracycline-based chemotherapy drug that works by inhibiting DNA transcription and replication to increase oxidative stress in tumor cells [8,9]. In clinical practice, it is commonly used as the first-line drug of choice, either in combination with other antitumor drugs or in combination with surgery and radiotherapy to eradicate tumors.…”
Section: Introductionmentioning
confidence: 99%